Precipitation behavior, mechanical properties, and corrosion resistance of rare earth–modified Al-Zn-Mg-Cu alloys. (June 2022) - Zhong, Huilong; Li, Shengci; Zhang, Zhiqian; Li, Dehua; Deng, Hongling; Chen, Jiqiang; Qi, Liang; Ojo, Olanrewaju A.
Abstract: In this study, we evaluated the microstructure, mechanical properties, and corrosion resistance of four types of 7055 alloys with and without the addition of rare earth elements (Er, Pr) elements. The results show a large number of coarse residual phase particles in the matrix of the 7055 alloy without the addition of rare earth elements, and the area proportion of residual phase is 3.56%; the proportion of low angle grain boundaries (LAGBs) after solid solution treatment is 31.1%. For the three other alloys that incorporate a rare earth element, the number of residual phases in the matrix is decreased, and the proportion of LAGBs is increased. As a result, the 7055 alloy with Pr (7055-Pr alloy) has the lowest number of residual phases, and the area proportion of residual phase is 1.41%; the 7055 alloy with Pr and Er (7055-Pr-Er alloy) has the highest proportion of LAGBs, which is 41.5%. Compared to the untreated 7055 alloy, the elongation and corrosion resistance of the three alloys with a rare earth element are increased. The increase in elongation is due to a reduction in the number of residual phases in the matrix, while the enhanced corrosion resistance is mainly due to the formation of Al3 (Er, Zr) particles as a result of adding Er, which could pin the grain boundaries. Thus, the migration of LAGBs to high angle grain boundaries (HAGBs) is inhibited, the LAGBs are retained, and the corrosion resistance of the alloy is enhanced. Graphical Abstract: ga1